A multigrid algorithm for the fan-beam ROI-tomography of contrast objects - Kulakov, I.Yu.; Vologin, D.A.; Pickalov, V.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2013)
A multigrid tomography algorithm (MG-ART) is proposed to perform iterative reconstructions in embedded regions and to produce high-resolution two-dimensional images inside a selected region of interest (ROI). This work presents estimates for the efficiency of the algorithm related to computing time and accuracy of reconstructions based on the results of numerical simulation. This multigrid algebraic algorithm can be implemented for various cases of complex observation systems, including seismic tomography studies and a number of industrial limited-angle tomography applications.